Assessment of Water and Wastewater Treatment Efficiency in Nigeria - Olatunde, Temitayo Samson; Isaiah, Lucky Cole; Obiezude, Melody Amarachi (Engineering Science Letter, 2024)
Water and wastewater treatment are vital in safeguarding public health and environmental sustainability. In Nigeria, various factors influence water and wastewater treatment systems' efficacy, including infrastructure conditions, management practices, and regulatory compliance. This study assesses the efficiency of water and wastewater treatment in Nigeria through a comprehensive evaluation of key parameters such as infrastructure conditions, water quality, treatment efficacy, and management efficiency. Data collected from 35 engineers involved in the water and wastewater sector were analyzed using statistical methods to identify areas for improvement. The quantitative descriptive statistical analysis summarized and interpreted numerical data using central tendency and variability measures. Results indicate significant disparities in infrastructure conditions and management practices, highlighting the need for strategic investment and policy interventions. Recommendations for policymakers include prioritizing infrastructure upgrades and enhancing stakeholder engagement to align with global standards. Future research directions emphasize the importance of longitudinal studies to track the effectiveness of interventions and explore innovative technologies for sustainable water management. Overall, this study provides valuable insights into the current state of water and wastewater treatment in Nigeria and offers actionable recommendations for enhancing efficiency and sustainability in the sector.